Some Types of Irregular Labeling of Diamond Networks on Ten Vertices - Nurdin Hinding; Ali Ahmad; Jusmawati Jusmawati (Department of Mathematics, Hasanuddin University, 2022)
There are three interesting parameters in irregular networks based on total labelling, i.e. the total vertex irregularity strength, the total edge irregularity strength, and the total irregularity strength of a graph. Besides that, there is a parameter based on edge labelling, i.e., the irregular labelling. In this paper, we determined the four parameters for diamond graph on eight vertices.